Diffuse Pulmonary Lesions Due to Invasive Fungal Infection in an Immune-capable Male: A Case Report - N. Radhakrishnan; Mathiyazhagan Narayanan (Dubai Medical Journal, 2025)
Introduction: Invasive fungal pulmonary infection is a fungal illness caused by many species of fungi, including Aspergillus, generally presenting as life-threatening hazards to people with compromised immune systems. Although instances in immunecompetent individuals are infrequent, a recently published report detailed active lung infection within an immune-competent patient at postmortem. We report a rare instance of invasive fungal infection (IFI) in an immune-capable male, exhibiting diffuse systemic lesions.